2003
DOI: 10.1046/j.1365-2702.2003.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Older South Asian patient and carer perceptions of culturally sensitive care in a community hospital setting

Abstract: This study describes the application of grounded theory to establish older, south Asian patient and carer views of service delivery in the UK. The purpose of the study was to inform the development of culturally sensitive services by defining the concept of cultural sensitivity from a user/carer perspective. The study took place in two community hospitals providing nurse-led intermediate care to a culturally diverse inner city population. Fifty-five per cent of the inner city population is of south Asian origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 22 publications
2
37
0
3
Order By: Relevance
“…Cultural diversities in relation to language, religion, dietary preferences, family structures, and beliefs related to health and care have impact on care-giving situations [5,6] .There have been several studies carried out from the caregivers' perspective which show that language obstacles are perceived as the main barrier to the contact between older immigrants and the health-care system. Nurses have described that many later-in-life immigrants only speak the language of their native country, though despite this, professional interpreters are seldom used in the care of older foreign-born patients [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…Cultural diversities in relation to language, religion, dietary preferences, family structures, and beliefs related to health and care have impact on care-giving situations [5,6] .There have been several studies carried out from the caregivers' perspective which show that language obstacles are perceived as the main barrier to the contact between older immigrants and the health-care system. Nurses have described that many later-in-life immigrants only speak the language of their native country, though despite this, professional interpreters are seldom used in the care of older foreign-born patients [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…Using a grounded theory approach, the third paper identified evaluated the perceptions of four patients and three relatives to culturally sensitive care were examined 38 . Although the study was limited in sample size the results indicated that patient and relatives viewed culturally sensitive care as a practice that respects individuality, maintains dignity and cares of the spiritual needs of the diverse groups.…”
Section: Resultsmentioning
confidence: 99%
“…L'étude de Browne (1995) auprès d'une population autochtone vient confirmer les résultats selon lesquels un rapport entre les attitudes et le comportement des prestataires de soins envers les femmes autochtones et l'incidence d'interactions cliniques respectueuses créaient des sentiments d'égalité et de dignité. Clegg (2003) a signalé que le concept de respect pour un individu était influencé en termes globaux par des interprétations politiques, sociales, économiques et religieuses.…”
Section: Discussionunclassified
“…Quoique la plupart des femmes originaires du Canada sont confrontées aux divers défis associés au cancer, ces défis prennent habituellement une ampleur accrue chez les immigrantes qui font peut-être face à des enjeux de migration et d'établissement, notamment aux défis associés au maintien de leurs propres croyances et pratiques tout en apprenant de nouvelles façons de se donner une vie stable dans leur nouveau pays (Gupta, Kumar & Stewart, 2002; Hilton et coll., 2001). Par exemple, les immigrantes doivent composer non seulement avec le diagnostic de cancer mais encore avec des enjeux liés à leur établissement au Canada tels que le fait d'avoir laissé leur famille étendue dans leur pays d'origine ou de prendre soin de membres de la famille et de s'adapter à la vie au Canada (Hilton et coll., 2001;Clegg, 2003;Singh, 2002).…”
Section: Contexteunclassified
See 1 more Smart Citation